2007
DOI: 10.1161/01.atv.0000255581.38523.7c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of the Homeostatic Chemokines CCL19 and CCL21 in Clinical and Experimental Atherosclerosis

Abstract: The abnormal regulation of CCL19 and CCL21 and their common receptor in atherosclerosis could contribute to disease progression by recruiting T-cells and macrophages to the atherosclerotic lesions and by promoting inflammatory responses in these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
107
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 30 publications
16
107
2
1
Order By: Relevance
“…10 -12 Furthermore, CCL19 and CCL21 expression is enhanced within atherosclerotic lesions of apolipoprotein E-deficient mice and in human atherosclerotic carotid plaques. 12 Although delayed entry of ccr7 Ϫ/Ϫ T cells to peripheral sites of antigen exposure may contribute to reduced atherosclerotic plaque development, we speculated that injection of ex vivo primed T cells may restore atherogenesis by compensating the loss of CCR7-coordinated contact between antigen-presenting DCs and naïve T cells in SLOs. Given the autoantigenic potential and critical importance of oxLDL in atherogenesis, we used this molecule for ex vivo maturation and activation of DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 -12 Furthermore, CCL19 and CCL21 expression is enhanced within atherosclerotic lesions of apolipoprotein E-deficient mice and in human atherosclerotic carotid plaques. 12 Although delayed entry of ccr7 Ϫ/Ϫ T cells to peripheral sites of antigen exposure may contribute to reduced atherosclerotic plaque development, we speculated that injection of ex vivo primed T cells may restore atherogenesis by compensating the loss of CCR7-coordinated contact between antigen-presenting DCs and naïve T cells in SLOs. Given the autoantigenic potential and critical importance of oxLDL in atherogenesis, we used this molecule for ex vivo maturation and activation of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, recent studies suggested that the enhanced endothelial expression of CCR7 ligands in chronically inflamed organs 10,11 or within atherosclerotic lesions 12 causes sustained T-cell recruitment to sites of inflammation. 13,14 Moreover, because CCR7 deficiency results in accumulation of T cells in inflamed tissues, 9,15 T-cell egress from sites of inflammation into draining lymph nodes also depends on CCR7.…”
Section: Clinical Perspective On P 1628mentioning
confidence: 99%
“…Nevertheless, aortic arch lesions were only observed in aortas from PI3K␥ ϩ/ϩ 3 LDLR Ϫ/Ϫ mice (2% of aortic arch area) and not in PI3K␥ Ϫ/Ϫ 3 LDLR Ϫ/Ϫ mice. Genetic data have provided evidence for the importance of chemokine receptors in the early steps of atherosclerosis, because they recruit monocytes 22 and T cells, [23][24][25] which have been identified recently as key regulators of atherosclerosis. Several reports show that T-helper type 1-driven responses promote plaque formation, 26 -28 whereas natural regulatory T cells are able to attenuate these responses and decrease the progression of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…68,69 A possible role for these chemokines and their receptor CCR7 in atherosclerosis has recently been addressed in 3 separate studies with contradictory findings. Compared to healthy controls, both CCL19 and CCL21 were increased in plasma and within carotid atherosclerotic lesions of patients with stable angina and even further in those with unstable CAD and in plaques of Apoe Ϫ/Ϫ mice.…”
Section: Immune-regulatory Chemokines Ccl19 and Ccl21 In Vascular Dismentioning
confidence: 99%